Segmenting Winter Sport Educational Tourism: An Experience Economy Approach - Wang, Xinghua; Chen, Hongbing (Technium Social Sciences Journal, 2025)
This study examines market demand patterns for winter sport educational tourism in Liaoning Province, China, through the lens of experience economy theory. Using the four-dimension experience framework (educational, entertainment, esthetic, and escapist experiences), we employ K-means clustering analysis to identify distinct market segments among 1,426 participants. Results reveal four distinct demand patterns: education-driven (35.2%), entertainment-oriented (28.4%), esthetic-immersive (21.8%), and escapist-relaxation (14.6%) segments. Each segment exhibits unique demographic characteristics, consumption behaviors, and experience preferences. The education-driven segment demonstrates the highest participation frequency and brand loyalty, while the escapist-relaxation segment shows the highest per capita spending. These findings challenge the traditional view of educational tourism as a homogeneous market and provide empirical evidence for the heterogeneity of consumer demands. The study contributes to experience economy theory by extending its application to educational tourism contexts and offers practical implications for developing differentiated marketing strategies in winter sports destinations.